Mapping the knowledge-consumer behavior nexus: a bibliometric analysis and systematic review - Qin Lingda Tan; Sharizal Hashim; Nor Liza Abdullah; Hafizah Omar Zaki; Zhangwei Zheng (Humanities & Social Sciences Communications)
Abstract In an era of sustainability transitions and digital transformation, consumer decisions are increasingly shaped by diverse forms of knowledge. Yet existing research remains fragmented, often narrowly focused on context-specific constructs such as environmental or digital literacy, with limited theoretical integration. To address this gap, this study combines bibliometric analysis of 571 peer-reviewed publications with a systematic review of 108 empirical studies. The bibliometric results reveal accelerating growth, expanding interdisciplinarity, and five dominant thematic clusters, including green behavior, digital trust, and persuasive knowledge cues. The systematic synthesis, guided by the TCCM framework, identifies critical gaps in regional coverage, knowledge conceptualization, and methodological diversity. Three theoretical pathways are distilled—attitudinal, cognitive-processing, and decision-oriented—explaining how knowledge shapes consumer behavior across domains. To enhance conceptual clarity, a two-dimensional framework is proposed, distinguishing between subjective and objective knowledge (cognitive form) and their attitudinal, informational, and decisional roles (functional role), while differentiating knowledge from adjacent constructs such as information, literacy, and belief. The study contributes a more integrated foundation for future research and offers actionable implications for designing knowledge-based strategies that support informed, inclusive, and sustainable consumption.